2021
DOI: 10.1002/joc.7296
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of CMIP5 and CMIP6 climate models in simulating summer rainfall in the Southeast Asian monsoon domain

Abstract: In this study, 28 climate models from the fifth phase of the Coupled Model Intercomparison Project (CMIP5) and 32 models from the sixth phase (CMIP6) have been evaluated for their ability to simulate large‐scale atmospheric circulations (using rainfall, wind fields, geopotential height, temperature, and moisture flux convergence) for the summer monsoon in Southeast Asia. Using a multi‐criteria decision making technique, models have been ranked based on 25 metrics which compare their performances with observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 70 publications
(84 reference statements)
2
22
0
Order By: Relevance
“…Khadka et al . (2021) ranked 28 climate models from CMIP5 and 32 climate models from CMIP6 for their ability to represent regional climate in Southeast Asia, with an emphasis on the simulation of the summer monsoon rainfall using 25 metrics. In the current study, 14 top‐ranking models from CMIP5 and 8 models from CMIP6 under the High‐Resolution Model Intercomparison Project (HighResMIP), for which data were available at the time of the analysis, have been considered.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Khadka et al . (2021) ranked 28 climate models from CMIP5 and 32 climate models from CMIP6 for their ability to represent regional climate in Southeast Asia, with an emphasis on the simulation of the summer monsoon rainfall using 25 metrics. In the current study, 14 top‐ranking models from CMIP5 and 8 models from CMIP6 under the High‐Resolution Model Intercomparison Project (HighResMIP), for which data were available at the time of the analysis, have been considered.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Another issue worthy of future studies is how the climate models perform in simulating the spatial patterns of early and peak summer rainfall anomalies over Asia. A few previous studies have evaluated climate models in simulating and projecting the summer rainfall over Southeast Asia (Tangang et al ., 2020; Khadka et al ., 2021). We plan to analyse the relation of East and South Asian summer rainfall to that over the ICP based on CMIP6 model outputs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This study concluded that MJO propagation is significantly improved in CMIP6 models compared to CMIP5 models. Several other studies have evaluated the performance of CMIP6 models to simulate the mean climate at both the global and the regional scales (Pattnayak et al, 2017;Wu et al, 2019;Xin et al, 2020;Khadka et al, 2021). There was a strong agreement that CMIP6 models showed an overall improvement in the skill scores of the climate patterns compared with CMIP5 models.…”
Section: Introductionmentioning
confidence: 88%